CREATION AND PERFORMANCE ON THE SATO INSTRUMENT (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
To highlight the theoretical, technological and performance capabilities of the Uzbek stringed musical instrument sato from the perspective of the development of national traditional art.